CONVERSION PROCESS IN ENGLISH LANGUAGE - Saytova Sarbinaz Umbetbaevna (Journal of new century innovations, 2023)
English is considered as one of the universal languages. It is growing considerably than before. There are more new age words nowadays compared to those in the previous era. English dictionary is thicker now and there are a wide range of dictionaries now than before. How can new words be created in languages? One of the processes of English word-formation is called conversion. It refers to an alteration in the function of a word, for instance when a noun comes to be used as a verb without any degradation or addition of affixes. Conversion is mainly found on nouns and verbs. Some examples of words constructed by conversion are look (verb to noun), email (noun to verb), native (adjective to noun).